Physio-Mechanical Assessment and Process Maps of Alsi10mg/Cu Material for Automobile Application - O. Olaniran; A. A. Adediran; A. A. Akinwande; O. S. Adesina; O. A. Mosadomi (Nigerian Journal of Technological Development, 2023)
In this study, copper (Cu) particles were used as a replacement to ceramic particles in AlSi10Mg matrix to lessen the brittleness often associated with ceramic particles when used as fillers in an aluminum matrix. AlSi10Mg was combined with 0, 2, 4, and 6% Cu and microwave sintering was performed at 300, 450 and 600 °C. The composites produced were subjected to physical tests measuring porosity, density, shrinkage, and relative density, as well as tensile testing. The microstructure was studied. Cu particles were dispersed at 2% and 4% sintering temperatures and clustered at 6% sintering temperatures, according to the microstructure images. The incorporation of 2% and 4% Cu decreased porosity, leading in increased yield, ultimate tensile strength, and elastic modulus. However, 6% Cu increased porosity, resulting in decreased yield and ultimate tensile strength. 2–6% Cu resulted in a linear rise in density, relative density, and shrinkage, as well as modulus of elasticity. Sintering temperature of 300 and 450 ˚C was favourable all parameters, however temperatures above 600 °C were detrimental to property responses. The proposed process map revealed diverse response values for varying input combination parameters; hence, a Cu dosage ≤ 4% at a sintering temperature of ≤ 450 °C is recommended.